Chromatin Immunoprecipitation and Sequencing (ChIP‐seq) Optimized for Application in Caenorhabditis elegans. Issue 7 (9th July 2021) - Sen, Ilke; Kavšek, Alan; Riedel, Christian G.
Abstract: Chromatin immunoprecipitation followed by next‐generation sequencing (ChIP‐seq) has become one of the most popular methods to study protein‐DNA interactions and can be used, for instance, to identify the binding sites of transcription factors or to determine the distributions of histones with specific post‐translational modifications throughout the genome. Although standard ChIP‐seq protocols work well in most experimental systems, there are exceptions, and one of these is the popular model organism Caenorhabditis elegans . Even though this system is very amenable to genetic and cytological methods, biochemical approaches are challenging. This is due to both the animals' cuticle, which impairs lysis as well as penetration by cross‐linkers, and the rather low protein and chromatin content per body weight. These issues have rendered standard ChIP‐seq protocols inefficient in C. elegans and raised a need for their improvement. Here, we describe improved protocols, with the most important advances being the efficient breakage of the C. elegans cuticle by freeze‐grinding and the use of a very sensitive sequencing library construction procedure, optimized for the relatively low DNA content per body weight of C. elegans . The protocols should therefore improve the reproducibility, sensitivity, and uniformity across tissues of ChIP‐seq in this organism. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Growth and harvesting of synchronized Caenorhabditis elegans Basic Protocol 2 : Chromatin immunoprecipitation (ChIP) Basic Protocol 3 : Library construction for Illumina sequencing